Regulation of Intimate Relations in Homes for Disabled as a Direction of Social Policy of Soviet State in 1920-1930s - A. S. Kovalev (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The relevance of the study is due to the need to study the formation and development of the Soviet state social policy in relation to the disabled population in 1920-1930-ies, including the regulation of sexual relations in homes for disabled. The question is raised about the limits of permissible interference of social security bodies in the private life of people in the care of the state. The views of society and the state on the problem of intimate relations between disabled people in social security institutions, the possibility of disabled people to start families with children are studied. Certain cases are analysed, allowing to consider the specific regulation of intimate relations in homes for disabled. Attention is paid to the opinions of representatives of Soviet eugenics on whether disabled people can have children. The data are given on how the issues related to pregnancy were solved among those living in homes for disabled. It is concluded that the Soviet authorities significantly limited the autonomy of disabled persons in homes for disabled, which was most clearly expressed in the prohibiting intimate relations. The author believes that for the disabled themselves, sexual relations remained a part of everyday life and were a kind of “proof of life” after being placed in a specialized social security institution.